Aveia branca (Avena sativa l.) como suplemento na terminação de novilhas em pastagem de aveia (Avena strigosa Schreb.) e azevém (Lolium multiflorum) - Azevedo Junior, Ricardo Lima de (2015)
This study aimed to investigate the effect of supplementation with white oats grain on the performance of heifers of 21 and 33 months of age on temperate pastures and the influence on productive parameters of pasture, performance, carcass and meat characteristis. Twenty-four Charolais x Nellore heifers, 12 with an average age of 21 months and average weight of 194.9 kg; and 12 with an average age of 33 months and average weight of 270.3 kg, were assigned to the treatments: With supplementation (WITH): heifers kept on pasture of oat + ryegrass receiving broken white oat grain at 0.6% body weight; Without supplementation (WITHOUT): heifers exclusively on pasture of oat + ryegrass. The experiment had a completely randomized design, in a 2 x 2 factorial arrangement (two treatments x two ages); data were analyzed using the SAS statistical package (2013). The chemical analysis of qualitative simulation of grazing and white oat grain showed no differences (P≥0.05), for supplementation and age of heifers. The forage mass was significantly different (P≤0.05) with mean values of 966.16 and 774.76 kg/ha for heifers WITH and WITHOUT supplementation, respectively. The supplementation promoted a greater production of pasture (7116.03 vs. 6251.14 Kg /DM/ha) (P≤0.05). The stocking rate was significantly different (P≤0.05) for animals of different ages, 785.51 and 577.53 kg body weight/ha for heifers of 21 and 33 months of age, respectively. The daily body weight gain was statistically different (P≤0.05), with mean values of 1.40 and 1.20 kg body weight for heifers WITH and WITHOUT supplementation, respectively. The slaughter weight was influenced by age; heifers of 36 months of age were heavier than heifers of 24 months of age (422.71 vs. 336.83 kg) (P≤0,05). Hot and cold carcass yields were not influenced by supplementation and age of heifers. Supplementation significantly affected the absolute weight of carcass fat (47.75 vs. 41.60) (P≤0,05). Heifers of 24 months of age, without supplementation, presented a lower fat thickness (1.72 mm), thus determining a greater carcass cooling loss (2.38 kg/100 kg carcass) (P≤0,05). There were interactions for the variables palatability, juiciness and tenderness of the meat.